2019
DOI: 10.1136/bmjopen-2018-024560
|View full text |Cite
|
Sign up to set email alerts
|

Association between perinatal interventional activity and 2-year outcome of Swiss extremely preterm born infants: a population-based cohort study

Abstract: ObjectivesTo investigate if centre-specific levels of perinatal interventional activity were associated with neonatal and neurodevelopmental outcome at 2 years of age in two separately analysed cohorts of infants: cohort A born at 22–25 and cohort B born at 26–27 gestational weeks, respectively.DesignGeographically defined, retrospective cohort study.SettingAll nine level III perinatal centres (neonatal intensive care units and affiliated obstetrical services) in Switzerland.PatientsAll live-born infants in Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…Two previous studies that examined the same hypothesis as this paper demonstrated better outcomes for babies born at a higher gestational age [12,13]. However, both studies suffered from selection bias.…”
Section: Study Findings In Contextmentioning
confidence: 58%
See 3 more Smart Citations
“…Two previous studies that examined the same hypothesis as this paper demonstrated better outcomes for babies born at a higher gestational age [12,13]. However, both studies suffered from selection bias.…”
Section: Study Findings In Contextmentioning
confidence: 58%
“…Data were collected over eight years, meaning there may have been changes in attitude within centres during the study period. They found important differences in survival and the odds of major neonatal morbidities, weaker evidence for an effect on mortality and neurodevelopmental impairment combined, and no evidence of a difference in neurodevelopmental impairment amongst survivors at two years of age [12]. There is a clear coherence in these results with our study: both support the idea that there is no relationship between the intensity of perinatal activity provided to extremely preterm babies and outcomes at two years of age for those born at a higher gestational age.…”
Section: Study Findings In Contextmentioning
confidence: 98%
See 2 more Smart Citations
“…20 Other studies documented a remarkable outcome variability between Swiss perinatal centres, which to a certain extent can be seen as the result of different local ethical approaches to providing intensive care to extremely preterm infants. 21 Finally, a comparison between Swiss perinatal centres with higher versus lower perinatal interventional activity at the limit of viability revealed that higher activity significantly decreased the risk of mortality and led to comparable outcomes regarding neurodevelopmental impairment at 2 years of life 22 and thereby matched observations from Sweden. 23 In this context, it is noteworthy that survival increased particularly at a GA < 25 weeks during our study period.…”
Section: Discussionmentioning
confidence: 76%